Influences of Temperature on the Conversion of Ammonium Tungstate Pentahydrate to Tungsten Oxide Particles with Controllable Sizes, Crystallinities, and Physical Properties - Asep Bayu Dani Nandiyanto; Heli Siti Halimatul Munawaroh; Tedi Kurniawan; Ahmad Mudzakir (Universitas Gadjah Mada, 2016)
The purpose of this study was to investigate influences of temperature on the conversion of ammonium tungstate pentahydrate (ATP) powder to tungsten trioxide (WO3) particles with controllable sizes, crystallinities, and physicochemical properties. In this study, we used a simple thermal decomposition method. In the experimental procedure, we explored the effect of temperature on the physicochemical properties of ATP by testing various heating temperatures (from 100 to 900 °C). The heated ATP samples were then characterized by a physical observation (i.e. color) and various analysis methods (i.e. a thermal gravimetric and differential thermal analysis, infrared spectroscopy, an X-ray diffraction, and a scanning electron microscope). Experimental results showed that increases in temperature had an impact to the decreases in particle size, the change in material crystallinity, and the change in physical properties (e.g. change of color from white, orange, to yellowish green). The relationships between the reaction temperatures and the physicochemical properties of the ATP were also investigated in detail along with the theoretical consideration and the proposal of the WO3 particle formation mechanism. In simplification, the phenomena can be described into three zones of temperatures. (1) Below 250 °C (release of water molecules and some ammonium ions).; (2) At 250-400 °C (release of water molecules and ammonium ions, restructurization of tungsten and oxygen elements, and formation of amorphous tungsten trioxide). (3) At higher than 400 °C (crystallization of tungsten trioxide). Since ATP possessed reactivity on temperature, its physicochemical properties changing could be observed easily, and the experimental procedure could be done easily. The present study will benefit not only for “chemistry and material science” but also potentially to be used as a model material for explaining the thermal behavior of material to undergraduate students (suitable used for a class and laboratory experiment and demonstration).